Electrocodeposition of Titanium and Gallium from 1-Butyl-1-Methylpyrrolidinium Trifluoromethanesulfonate. Issue 12 (4th September 2020) - Borisenko, N.; Ispas, A.; Wu, Q.; Carstens, T.; Behrens, N.; Karg, J.; Engemann, T.; Endrikat, A.; Bund, A.; Endres, F.
Abstract : Electrochemical co-deposition of gallium and titanium on copper and gold substrates from the ionic liquid 1-butyl-1-methylpyrrolidinium trifluoromethanesulfonate was investigated in the temperature range from 25 °C to 140 °C. Crystalline gallium-titanium alloys were obtained by annealing the deposits at 800 °C for 16 h. X-ray diffraction performed on the annealed specimens confirmed the formation of crystalline phases. In situ quartz crystal microbalance experiments gave further insight into the initial stages of gallium-titanium co-deposition. One can tune the composition of the films by changing the deposition potential or the deposition technique. Gallium rich films (with more than 60 wt%) were obtained by potentiostatic depositions at 140 °C. We could show that no elemental titanium can be electrodeposited from bis(cyclopentadienyl)titanium(IV) bis(trifluoromethanesulfonate) in 1-butyl-1-methylpyrrolidinium trifluoromethanesulfonate. The addition of GaCl3 to the electrolyte facilitated the reduction of Ti(IV) species.